Social Protection, Poverty and the Post-2015 Agenda - Fiszbein, Ariel; Kanbur, Ravi; Yemtsov, Ruslan (World Bank, Washington, DC, 2013)
Social protection is absent from the Millennium Development Goals (MDGs), and only recently has gained some prominence in the post-2015 discourse. In the past quarter century, however, rising inequality has often accompanied economic growth. At the same time, the growing importance of risk and vulnerability on the wellbeing of the poor has been recognized. Further, there is now a consensus on adopting more ambitious goals on poverty reduction. Defining social protection as a collection of programs that address risk, vulnerability, inequality and poverty through a system of transfers in cash or in kind, this paper argues that social protection needs to be on the post-2015 agenda as a key element of the discourse. It provides an empirical overview of social protection around the world based on the World Bank's Atlas of Social Protection: Indicators of Resilience and Equity (ASPIRE) data set. Focusing on the goal of ending poverty, the paper estimates that social protection programs are currently preventing 150 million people from falling into poverty. Based on the data set, the paper develops, tentatively and for discussion, a set of candidate goals, indicators and targets for the acceleration of poverty reduction through social protection. The authors ask what it would take for social protection programs to contribute to halving the poverty gap in a country. They show that if all countries could achieve the actual poverty reduction efficiency already observed in the top quartile of countries, then 70 percent of the countries in the sample could achieve this goal. However, for 30 percent of the countries, even reaching the top quartile on efficiency will not be enough -- for these countries, the issue is one of budgetary adequacy.